A REVIEW OF TREATMENT ASPECTS OF COMPUTER VISION SYNDROME (CVS) THROUGH AYURVEDA (AYUSHDHARA, 2019)
Computers have become a critical component of our life. In many situations, everyone indispensably needs to use a computer. Different careers depend purely on computer use since the arrival of games, different software programs, etc. The utility of computers has been extended to such a proportion that people use a computer for more than 8 hours a day. Though inevitable, it damages the eye and circumjacent muscles as the computer causes train on eyes. Most of these symptoms are due to the dryness of eyes and reduced blinking. Shalakya Tantra shares the maintenance of healthy eyesight through diversified Kriyakalpas. Kriyakalpas include Tarpana, Putapaka, Ashchotana, Anjana, Vidalaka, Lepa, etc. All these Kriyakalpas are utilized for the maintenance of a healthy eye. When an imbalance of Tridosha occurs in different Mandalas and Patalas, these Kriyakalpas are used to restore equilibrium in the status of Doshas and result in Samprapti-vighatana. Computer Vision Syndrome is not mentioned directly in Ayurvedic classics but it can be compared with symptoms of Shushkakshipaka of Sarvaksiroga. Acharya Vagbhata has mentioned cooling and rejuvenating therapies for eyes affected by bright light, high-voltage electric spark and heat exposure. Frequent eye examinations and appropriate viewing habits help to prevent the development of the symptoms of CVS. Nasya is highly effective in CVS if it is performed systematically. Thus, Ayurveda is an effective medical system that is crucial to keep your eyes healthy.